Re-imagining Operatic "Objects": Commentary on Neumann’s Phenomena, Poiesis, and Performance Profiling: Temporal-Textual Emphasis and Creative Process Analysis in Turandot at the Metropolitan Opera - Volioti, Georgia (Empirical Musicology Review, 2018)
Objects come in all sorts of shapes, sizes and forms. The notion of musical works as objects, represented by their written scores, has proved to be effete and limiting to the study of music as diverse social-cultural practice and performed craft. The past two decades have witnessed considerable efforts to renew conceptual and methodological tools, and Neumann's study makes a valuable contribution to this effect. This commentary responds to some issues raised by Neumann's article in relation to the notion of musical "object". Specifically, I retrace the shift from a score-based to a process-oriented musicology geared towards performances, placing the concerns of contemporary opera studies within this broader disciplinary change. I consider some implications of technology in mediating new operatic objects for discourse. Finally, I reflect on some of the inherent dangers of objectifying performance in empirical analyses.